Evaluation of Scrab Conveyor Machine Performance at Pt Dharma Polimetal Tbk. Hyundai Plant Using The Six Sigma (Dmaic) Method - Avito Riza Yusuf; Ahmad Fikrie (Journal of Applied Mechanical Engineering Innovation, 2026)
This study aims to evaluate the performance of scrap conveyor machine in Stamping production line at PT Dharma Polimetal Tbk . Hyundai Plants. The main problem raised in this research is the high level of downtime on the conveyor machine, which negatively impacts the effectiveness of the production process and contributes to an increase in operational costs. Therefore, this research was conducted to identify the root causes of the problem and formulate applicable and sustainable improvement solutions. The method used in this research is the Six Sigma approach with DMAIC (Define, Measure, Analyze , Improve, Control) stages. Analysis is done by utilizing downtime data using Pareto Diagram and Fishbone tools to identify problem priorities. The Improve stage is carried out with corrective actions in the form of hopper redesign, installation of conveyor covers, and improvement of system wiring and automatic sensors to improve the reliability of the conveyor system. The results showed that corrective actions were able to significantly reduce the duration of downtime, especially in the bent chain plate problem, from 310 minutes to only 50 minutes in August 2024. This finding proves that the application of Six Sigma methods is effective in improving the operational efficiency and performance of scrap conveyor machines. Thus, this data-driven improvement strategy makes a real contribution to increasing the company's productivity and competitiveness.